"Criminal law, criminology and criminal administration / edited by K. D. Gaur" - "Gaur, K. D. (ed.)" (New Delhi, 1992)
This book covers important areas of topical significance in the field of criminal law, criminology and criminal administration and discusses the latest judicial and administrative technique of creativity through development of case laws and juristic expositions and innova tions in this important branch of knowledge which closely touches and concerns every man in his day-to-day affairs, Keeping in view the broad objective, an effort has been made to include literature covering various aspects of criminal law, criminology and human right including other social sciences related materials in the socio-economic context.
Keywords: Criminal law